SARS-CoV-2 recurrence and probable reinfection: outcome of a descriptive surveillance in a Nigerian tertiary hospital - Alasia, Datonye Dennis; Maduka, Omosivie; Wariso, Kennedy; Awopeju, Temitayo; Emuh, Faith (International Journal of Research in Medical Sciences, 2021)
Background: The reports of SARS-CoV-2 reinfection have increased. This stimulates the need for surveillance in diverse populations to establish the extent of reinfections and the challenges to diagnosis. Methods: A retrospective descriptive survey aimed at identifying probable SARS-CoV-2 reinfections using established criteria and proposed definitions was performed at a tertiary hospital in South-South, Nigeria. Results: The study found two cases for evaluation of reinfection. One case was identified as probable reinfection, pending the outcome of gene sequencing, while the second case was categorized as recurrence. The limited access to routine genetic sequencing for confirmation of reinfection was identified as a key challenge. Conclusions: Probable SARS-CoV-2 reinfections occur in Nigeria. Systematic surveillance of SARS-CoV-2 testing at the state and country-level is advocated to have a more accurate estimate of the burden of reinfections in the country. Access to genetic sequencing should be scaled up in Nigeria.